The influence of complaint handling, security and e-service quality on user loyalty e-wallet DANA among college students in Padang City - Muhammad Aditya Fajar; Engriani, Yunita (Marketing Management Studies, 2024)
This research was conducted with the aim of analyzing and determining the influence of Complaint Handling, Security and E-Service Quality on User Loyalty among Students in Padang City. The type of research carried out is quantitative research. The population of this research is students who live in Padang City with a sample size of 150 respondents. In this research, analysis was carried out using SPSS with SPSS 27. The result of this research showed that (1) Complaint Handling had a positive and significant effect on E-Wallet Dana User Loyalty, (2) Security had a positive and significant effect on E-Wallet Dana User Loyalty, (3) E-service Quality has a negative effect on E-Wallet Dana User Loyalty.